HIV-1 increases TLR responses in human primary astrocytes - Serramía, M Jesús (Sci Rep, 2015)
Astrocytes are the major glial cell within the central nervous system and have a number of important physiological properties related to brain homeostasis. They provide trophic support to neurons and are immune cells with key roles during states-of-inflammation. The potential for production of proinflammatory cytokines and its consequences has been studied in the context of HIV-1 infection of normal human astrocytes (NHA). NHA express TLR3, TLR4, and TLR5. TLR3 ligation induced the strongest proinflammatory polarizing response, characterized by generation of high levels of TNF-α, IL-6, and IL-8. HIV-1 increased the transient production of key inflammatory mediators, and exposure to LPS of HIV-1-infected cells increased significantly the cytokine secretion. We confirmed that it is necessary viral gene expression from the moment of pretreatment with antiretrovirals inhibited totally HIV-1-induced TLR response. The higher response to LPS from HIV-1-infected cells did not correlate with TLR4 or MyD88 increased expression. LPS responsiveness of infected cells parallels MHC class II expression, but not CD14. HIV-1-infected NHA present increased sensitivity to the proinflammatory effects of LPS. If this phenomenon occurs in vivo, it will contribute to the immunopathogenesis of this disease and may ultimately offer novel targets for immunomodulatory therapy.